The association between metabolic syndrome severity and frailty risk in patients with rheumatoid arthritis: a cross-sectional study - Yuefang Liu; Yan Xin; Weiwei Wang; Wei Feng; Lei Zhang; Yang Zhao; Youzhuang Zhu (Arthritis Research & Therapy)
Abstract Background Rheumatoid arthritis (RA) is a chronic autoimmune disease in which systemic inflammation may put individuals at increased risk of developing frailty and metabolic syndrome (MetS). However, the relationship between MetS severity and frailty remains poorly understood in individuals with RA. Further, traditional MetS diagnostic methods do not assess severity and thus may lack sensitivity in capturing subtle metabolic abnormalities. Methods In this cross-sectional study, data from the National Health and Nutrition Examination Survey (2003–2018) were used to construct weighted multivariable logistic regression models to explore the risk association between MetS severity and frailty in RA patients. Restricted cubic spline analysis was used to examine non-linear correlation between MetS severity and frailty. We also conducted subgroup analyses and interactions as well as sensitivity analysis to evaluate the robustness of results. Results A total of 802 RA patients were included in this study, among whom 442 were identified as frail (52.05%). RA patients with higher MetS severity had significantly increased frailty risk [adjusted odds ratio (aOR): 1.26; 95% CI: 1.09–1.46; p = 0.003]. There was a non-linear relationship between MetS severity and frailty (p for overall < 0.001; p for non-linear < 0.001), with an inflection point at 0.089. When MetS z-score was < 0.089, there was no significant association between MetS z-score and frailty (p > 0.05), whereas the association was positive for scores ≥ 0.089 (aOR: 1.68; 95% CI: 1.30–2.17; p < 0.001). The risk of frailty increased significantly with increasing MetS severity among alcohol drinkers (aOR: 1.43; 95% CI: 1.19–1.71; p < 0.001) compared with non-drinkers (aOR: 0.97; 95% CI: 0.73–1.29; p = 0.085). Sensitivity analysis confirmed robustness of the association between MetS severity and risk of frailty. Conclusions We identified a significant association between MetS severity and frailty risk in patients with RA. As MetS severity increased, the risk of frailty was higher among alcohol drinkers compared to non-drinkers. Clinicians should enhance frailty screening and management in patients with RA by incorporating assessments of MetS severity into routine practice.